Corporate diversification, board diversity and stock-price crash risk: Evidence from publicly listed firms in Malaysia - Lee, Kian Tek *; Hooy, Chee Wooi; Ooi, Chai Aun (Universiti Putra Malaysia, 2019)
This study investigates whether corporate diversification can be a predictability variable contender for future stock-price crash risk. Using a sample of Malaysian firms based on 2010-2015 data, our study shows evidence of the mitigating effect of diversification on crash risk, consistent with the theory of coinsurance effect. However, our further analysis shows that the mitigating effect of diversification on crash risk is only evident on highly diversified firms but not on firms of low to moderate degree of diversification. This finding is aligned with the dominant view of the existence of crash risk following the managerial bad-news hoarding model. Furthermore, our study finds that the mitigating effect of diversification is more pronounced for firms with board diversity in gender which is in support of the notion of board diversity in promoting corporate governance. Our findings are useful to firms (and shareholders) who want to manage “tail risk” in stock prices and to investors who want to incorporate crash risk as parts of their portfolio and risk management decisions.